2018
DOI: 10.2147/dddt.s181939
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein induces apoptosis and autophagy of breast cancer cells via inhibiting PI3K/AKT pathway in vivo and vitro

Abstract: PurposeBaicalein, a widely used Chinese herbal medicine, has shown anticancer effects on many types of human cancer cell lines. However, little is known about the underlying mechanism in human breast cancer cells. In this study, we examined the apoptotic and autophagic pathways activated following baicalein treatment in human breast cancer cells in vitro and in vivo.Materials and methodsIn in vitro study, we used MTT and clone formation assay to confirm the inhibitory role of baicalein on proliferation of MCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(121 citation statements)
references
References 39 publications
11
102
0
1
Order By: Relevance
“…BA also increased the release of cytochrome c and Aif from mitochondria to cytoplasm. These results suggested that BA activated mitochondrial apoptotic pathway and induced apoptosis, which is consistent with other studies [18,20,21,34]. Moreover, BA increased mitochondrial fragmentation, promoted mitochondrial fission related protein expressions, and impaired mitochondrial functions such as cellular ATP depletion, decrease of mitochondrial mass and decrease of mitochondrial respiratory chain related protein expressions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…BA also increased the release of cytochrome c and Aif from mitochondria to cytoplasm. These results suggested that BA activated mitochondrial apoptotic pathway and induced apoptosis, which is consistent with other studies [18,20,21,34]. Moreover, BA increased mitochondrial fragmentation, promoted mitochondrial fission related protein expressions, and impaired mitochondrial functions such as cellular ATP depletion, decrease of mitochondrial mass and decrease of mitochondrial respiratory chain related protein expressions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have found that BA induces apoptosis and autophagy in multiple cancer cells [18,20,21,26], but the underlying mechanisms are still unclear. In the present study, we demonstrated that BA induced apoptosis and autophagy via activating Drp1-mediated mitochondrial fission in lung cancer A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…34 It is also effective in inhibiting UVB-induced photodamage in keratinocytes by harvesting reactive oxygen species, 20 reducing the increased apoptosis rate and suppressing oxidative DNA adducts, in which process the relevant cytokine secretion and the expression of several genes like p53 and p21 were reduced. 35 Meanwhile, baicalin has been shown to induce autophagy in a variety of cell types including hepatocellular carcinoma cells, 26,36 breast cancer cells, 37 and even mice brain. 38 In this context, we examined whether baicalin could protect fibroblast cells against UVB radiation via reducing apoptosis and inducing autophagy, and explored if the underlying mechanism of autophagy induction is via activation of AMPK and downregulation of mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…The controls (untreated photoactivated and nonphotoactivated cells) displayed a physiological level of ca. 10% of apoptotic cells, corresponding with [61,62], but exhibited no necrosis ( Figure 6, SI Table S1). Similar results were detected for compound 1 at 0.1-1 µM concentration without photoactivation.…”
Section: Evaluation Of Cell Deathmentioning
confidence: 99%